2022
DOI: 10.1002/csr.2338
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the moderating effects of corporate social responsibility performance under mimetic pressures. An international analysis

Abstract: The purpose of this article is threefold. Firstly, it is aimed at ascertaining whether, in seeking social legitimization, companies disclose CSR information as a response to mimetic pressures. Secondly, it ascertains whether, by seeking economic legitimization, companies with superior CSR performance disclose CSR information to differentiate themselves from low-performing counterparts. Thirdly, it examines the moderating effects of CSR performance in the relationship between mimetic pressures and CSR disclosur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
12
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 78 publications
3
12
0
Order By: Relevance
“…Turning to the control variables, both the coercive pressures (Coercive) and the normative pressures (Normative) have a positive effect (φ 3 = .186 and φ 4 = 4.232, respectively, p <.01) on the dissemination of information about SDGs, in line with previous literature (Galleri et al, 2021;Zampone, Sannino, & García-Sánchez, 2022).…”
Section: Main Effectssupporting
confidence: 87%
See 2 more Smart Citations
“…Turning to the control variables, both the coercive pressures (Coercive) and the normative pressures (Normative) have a positive effect (φ 3 = .186 and φ 4 = 4.232, respectively, p <.01) on the dissemination of information about SDGs, in line with previous literature (Galleri et al, 2021;Zampone, Sannino, & García-Sánchez, 2022).…”
Section: Main Effectssupporting
confidence: 87%
“…Next, the second greatest effect is exerted by Mimetic_FB (φ 1 = .671; p < .01), confirming that frequency-based imitation drive companies to conform their SDG reporting practices to those of the other companies operating in the same industry. Finally, although with a lower magnitude (φ 1 = .0122; p < .01), trait-based imitation is the third form chosen by companies facing uncertainty.Accordingly, we accept H1, corroborating previous accounting research findings(Amor-Esteban et al, 2018a;Cubilla-Montilla et al, 2020;Galleli et al, 2021;Martínez-Ferrero & García- Sánchez, 2017;Zampone, Sannino, & García-Sánchez, 2022).…”
supporting
confidence: 90%
See 1 more Smart Citation
“…Considering that factors such as a firm's financial condition, operational status, and governance level can influence ESG disclosure decisions, larger and more profitable firms are more willing to disclose ESG information to maintain a good image (Clarkson et al, 2011; Zampone et al, 2023). Following the studies of Dhaliwal et al (2012) and Lin and Rao (2009), we selected 10 variables that cover the three aspects of a firm's financial condition, operational status, and governance level as control variables to reduce empirical biases.…”
Section: Methodsmentioning
confidence: 99%
“…Secondly, the influence of internal corporate factors on ESG disclosure is also significant. Existing studies have found that, apart from larger and more profitable firms being more willing to disclose ESG information to maintain a good image (Clarkson et al, 2011; Knox et al, 2015; Zampone et al, 2023), the characteristics of corporate governance structures also play an important role in strategic social responsibility information disclosure (Zheng et al, 2015). Sun et al (2021) found that board interlocks have a demonstrative effect on ESG behavior, promoting the diffusion of ESG behavior among firms and thereby affecting the quality of associated firms ESG disclosure.…”
Section: Research Background and Hypothesis Developmentmentioning
confidence: 99%